3‐D Analog Modeling Constraints on Rifting in the Afar Region. Issue 10 (9th October 2020) - Khalil, Hany M.; Capitanio, Fabio A.; Betts, Peter G.; Cruden, Alexander R.
Abstract: Rifting in the Afar region is considered to be the only known example of the formation of an incipient divergent triple junction. Taking the Afar region as an example, we use three‐dimensional lithospheric‐scale laboratory experiments to constrain the factors controlling the structure and the tectonic evolution of the area. We systematically evaluate the role of different preexisting heterogeneities, such as those due to plume head impingement or inherited weak structures, and different kinematic boundary conditions, such as orthogonal versus rotational extension. The interaction between these inherited heterogeneities and the tested boundary conditions results in a range of complex rift geometries and structural features, such as rift segmentation and ridge jumps, which are comparable to those observed in the Afar region. At the plate scale, only under rotational extension, consecutive rift zones intersecting at high angles develop akin to the along‐axis segmentation in the Red Sea and the Gulf of Aden. Under orthogonal extension, the dominant rifting trend is perpendicular to the stretching direction. Preexisting weaknesses, including that due to a mantle plume, trigger different rifting styles and influence the geometry of large‐scale continental breakup. When compared to the Afar region, our results suggest that differing the degree of stretching, following the rotation of the Arabian plate since the Oligocene, led to the rifting in the Red Sea and the Gulf of Aden and likely did not cause the formation of the Main Ethiopian Rift. Key Points: 3‐D analog modeling help testing the role of preexisting lithospheric weaknesses under orthogonal and rotational extension on the Afar Inherited heterogeneities, including that of plume head impingement, influence the geometry of the continental breakup in the Afar region Rifting in the Red Sea‐Afar‐Gulf of Aden is mostly the result of the rotational far‐field tectonic forces imposed by Arabia